Modification of Structure and Tribological Properties of the Surface Layer of Metal-Ceramic Composite under Electron Irradiation in the Plasmas of Inert Gases; IOP Conference Series: Earth and Environmental Science; Vol. 115 : Ecology and safety in the technosphere - Ovcharenko V. E. Vladimir Efimovich; Ivanov K. V.; Mokhovikov A. A. Aleksey Aleksandrovich; Yu B.; Yu Xu; Zhong L. (2018, 2018)
Title screen